Measuring and analyzing the path loss in radio wave link used in Keretapi Tanah Melayu Berhad (KTMB) / Mohd Hisyam Mohd Ariff - Mohd Ariff, Mohd Hisyam (2005)
This project thesis presents the measuring and analyzing the path loss in radio wavelink. This system will be based upon the Keretapi Tanah Melayu Berhad (KTMB) Train Radio System. Basically, KTMB uses both analogue and digital system to transmit the signal. The main objective of this project is to study the effectiveness of the surrounding object relating to the signal received at the train antenna in open spaces and places with high-rises building that closer to the train railway, and also to test whether the of path loss model that are used in this project is suitable to be used in Keretapi Tanah Melayu Berhad (KTMB) The whole project actually discussed a focusing parameter of the path loss model such as types of area, population and also surrounding objects. In this paper, literature review is provided and several path loss models such as Free Space Path Loss, Okumura-Hata Path Loss and British Urban Formula are implemented for KTMB Train Radio System. These path loss models are very important in the design of radio wave communication systems.